Pengaruh Lingkungan Keluarga dan Fasilitas Belajar Terhadap Prestasi Belajar Metematika Kelas VIII SMP Negeri 3 Lingsar pada Materi Lingkaran Tahun Ajaran 2020/2021 - Nurul Pratiwi; Sripatmi Sripatmi; Nyoman Sridana; Amrullah Amrullah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to determine the effect of the family environment and learning facilities on the mathematics learning achievement of class VIII SMP Negeri 3 Lingsar on the circle material. The type of research used is causal comparative (ex post facto) with a quantitative approach, the data collection techniques used in this study are questionnaires and tests. The population in this study were all students of class VIII, totaling 120 students and the sample used was 24 students. Meanwhile, the data analysis technique used was simple linear regression and multiple linear regression which had previously been tested for analysis prerequisites, namely normality test, linearity test, and multicollinearity test. The results obtained indicate that the family environment and learning facilities have a significant effect on mathematics learning achievement for class VIII SMP Negeri 3 Lingsar on the Circle material with an effect of 77.70%, while the remaining 22.30% is influenced by variables not examined.